Resisting Financial Predation: A Community-Based Financial Literacy Strategy to Mitigate Illegal Investment Risk in Coastal Indonesia - Shalihah, Mar'atun; Amin, Deny Yarusain; Yaman, Afdhal; Waluyo, Bambang; Ningsih, Tri Fitria (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2025)
This study develops a financial literacy–based strategy to mitigate illegal investment risks in vulnerable coastal communities using a Financial Vulnerability Index (IKF) and a Multi-Criteria Decision-Making (MCDM) approach integrating AHP and TOPSIS. Conducted in three Central Maluku villages, the IKF combines economic vulnerability, financial literacy, and access to finance. Findings show Wailulu and Asilulu as highly vulnerable (IKF >0.90), while Tulehu is more resilient. AHP-TOPSIS results rank community- based training as the most effective strategy, followed by local media literacy and fishermen cooperative engagement. These findings validate the Community-Embedded Literacy Delivery Model (CELDM), highlighting the effectiveness of localized, participatory approaches. The study informs inclusive and adaptive financial literacy policies targeting high-risk populations. Keywords: illegal investment; financial literacy; community-based strategy; AHP-TOPSIS; coastal vulnerability; financial inclusion   Abstrak Penelitian ini mengembangkan strategi mitigasi investasi ilegal berbasis literasi keuangan bagi komunitas pesisir rentan dengan menggabungkan Indeks Kerentanan Finansial (IKF) dan pendekatan MCDM (AHP-TOPSIS). Studi dilakukan di tiga desa di Maluku Tengah, dengan IKF mencakup dimensi kerentanan ekonomi, literasi keuangan, dan akses keuangan. Wailulu dan Asilulu tergolong sangat rentan (IKF > 0,90), sementara Tulehu lebih tangguh. Hasil AHP-TOPSIS menunjukkan pelatihan komunitas sebagai strategi paling efektif, diikuti kampanye media lokal dan kemitraan koperasi nelayan. Temuan ini menguatkan Model Penyampaian Literasi Berbasis Komunitas (CELDM), dan memberikan dasar bagi kebijakan literasi keuangan yang inklusif dan kontekstual. Kata kunci: investasi ilegal; literasi keuangan; strategi berbasis komunitas; AHP-TOPSIS; kerentanan pesisir; inklusi keuangan